CONSUMER PREFERENCE OF DOMESTIC VERSUS FOREIGN BRANDED CLOTHING IN A DEVELOPING COUNTRY: THE CASE OF TURKEY - Kapali, Didem (2006)
The focus of this dissertation is to analyse the attitudes of Turkish women who belongs to different age groups when purchasing domestic and foreign branded clothing. The effect of country of origin, brand versus country of origin, country image, brand image, ethnocentrism and conspicuous consumption have been evaluated in order to understand consumers' preferences of foreign versus domestic brands in clothing.